Standards of Specialized Diabetes Care / Edited by Dedov I.I., Shestakova M.V., Mayorov A.Yu. 11th Edition - I. Dedov; M. Shestakova; A. Mayorov; N. Mokrysheva; E. Andreeva; O. Bezlepkina; V. Peterkova; E. Artemova; P. Bardiugov; D. Beshlieva; O. Bondarenko; F. Burumkulova; et al. (Сахарный диабет, 2024)
Dear Colleagues!We are glad to present the 11th Edition of the Standards of Specialized Diabetes Care. These evidence-based guidelines were designed to standardize and facilitate diabetes care in all regions of the Russian Federation.The Standards are updated on the regular basis to incorporate new data and relevant recommendations from national and international clinical societies, including World Health Organization Guidelines (WHO), International Diabetes Federation (IDF), European Association for the Study of Diabetes (EASD), American Diabetes Association (ADA), American Association of Clinical Endocrinologists (AACE), International Society for Pediatric and Adolescent Diabetes (ISPAD) and Russian Association of Endocrinologists (RAE). Current edition of the “Standards” also integrates results of completed randomized clinical trials, as well as findings from the national studies of diabetes mellitus (DM), conducted in close partnership with a number of Russian hospitals.Latest data indicates that prevalence of DM in the world increased during the last decade more than two-fold, reaching some 537 million patients by the end of 2021. According to the current estimation by the International Diabetes Federation, 643 million patients will be suffering from DM by 2030 and 783 million by 2045.Like many other countries, Russian Federation experiences a sharp rise in the prevalence of DM. According to Russian Federal Diabetes Register, there are at least 4 962 762 patients with DM in this country on 01.01.2023 (3,42% of population) with 92,3% (4 581 990) – Type 2 DM, 5,6% (277 092) – Type 1 DM and 2,1% (103 680) – other types of DM, including 8 758 women with gestational DM. However, these results underestimate real quantity of patients, because they consider only registered cases. Results of Russian epidemiological study (NATION) confirmed that 54% of patients with Type 2 DM are undiagnosed. So real number of patients with DM in Russia is 11-12 million patients (about 7% of population). This is a great long-term problem, because a lot of patients are not diagnosed, so they don’t receive any treatment and have high risk of vascular complications.Severe consequences of the global pandemic of DM include its vascular complications: nephropathy, retinopathy, coronary, cerebral and peripheral vascular disease. These conditions are responsible for the majority of cases of diabetes-related disability and death.In accordance with the Federal Law № 489-FZ of 25.12.2018 medical care should be provided on the basis of the clinical recommendations. Therefore, clinical recommendations posted in the rubricator of the Ministry of Health of the Russian Federation (https://cr.minzdrav.gov.ru) being the priority.This edition of the Algorithms for Specialized Care for Patients with Diabetes Mellitus contains the main information from the clinical guidelines for the management of diabetes mellitus in adults and children (“Type 1 Diabetes in Children (2022)”, “Type 1 Diabetes in Adults (2022)”, “Type 2 diabetes mellitus in children (2021)”, “Type 2 diabetes mellitus in adults (2022)”), as well as the updated data.New information has been added about indications for using of antihyperglycemic drugs and their instructional restrictions; algorithm of treatment of type 2 diabetes mellitus has been updated; clarifications have been made on the range of glycemic control in pregnant women; information on the treatment of diabetic complications and the management of pediatric patients has been added. In 2023, Russian diabetology suffered an unbearable loss - Alexander Yuryevich Mayorov, who was the executive editor of the previous issues and an active participant of the work on all the previous editions of “Algorithms” from the moment they were founded, passed away. This publication is dedicated to the memory of Alexander Yuryevich, who was an example of the service to patients and medicine, a friend, teacher, mentor, generously sharing his knowledge and the sample of the execution of the medical duty to all of us. On behalf of the Working Group